Senses of death in children's literature and the approaching possibilities of the subject with children in pandemic times - Jessiara Leandro de Souza; Bethania Medeiros Geremias (Pesquisa e Ensino, 2021)
In order to build strategies for addressing the theme of death, due to the COVID-19 pandemic, we proposed to analyze how the meanings of death are portrayed in children's literature. To this end, two children's books were selected: Forever in my heart, by Ziraldo (2002) and Menina Nina: two reasons for not crying, by Mauricio de Sousa and Paula Furtado (2019). In the article we present bibliotherapy; the meanings of death in different contexts and we bring examples from books. Based on some theoretical-methodological discussions of linguistics and Discourse Analysis, we performed a description of the works, focusing on verbal and non-verbal aspects. We found that the selected books can help explain the multiple ways of understanding death, thus, they can help parents to talk to their children and teachers to develop didactic strategies, following BNCC guidelines for Early Childhood Education and early years of Elementary School.